3PC-030 93% oxygen: 2 years' evaluation of an innovative technology. (2nd March 2018) - Ceravolo, G; Lecis, M; Viglione, E; Strobino, S; Martinengo, S; Rosa, A; Novello, S; Medail, M; Buffa, C
Abstract : Background: In Italy, oxygen is considered a drug. Since January 2010, therapeutic oxygen must have a Marketing Authorisation Holder (MAH). Pharmaceutical spending is one of the most important health expenditure items and it is necessary to take actions to support the National Health System (NHS). Purpose: From September 2015, 93% oxygen self-production HTA project was established, as reported in the PH-EUR monograph n. 2455/4/2011. In fact it can be produced in hospital, is an official preparation and it does not require a MAH. The 2 years of technology use were analysed. Material and methods: Since September 2015, there is a liquid oxygen concentrator in a hospital. The hospital pharmacy manages the drug delivery, while the technical office maintains and performs the quality controls according to regulations. In case of service interruption, oxygen supply is guaranteed by the back-up source (back-up cylinders) providing 99% oxygen gas. Drug consumption, maintenance work and secondary oxygen source gas consumption were analysed. A randomised controlled clinical trial (RCT) was conducted for 12 months, giving 93% or 99% oxygen, defining clinical efficacy outcomes (L/min flow reduction, O2 saturation, EGA T0-entry/T1-discharge) and management security (chemical quality/system abnormalities). Results: In 2014, oxygen expenditure was €55 000 (18, 000 m 3 ), while in 2016, the gaseous oxygen spending for back-up was about €2200. The annual saving is around €35, 000, including the purchase of technology. The clinical trend among the cases/controls demonstrates an overlapping of clinical efficacy. To ensure the proper functioning of the system, the technical office required three 'visit reports' and three 'service reports'. In addition to continuous monitoring of oxygen content, five samples were taken and product analysis of these were also performed by a specialist laboratory. Conclusion: Two years' later, a positive assessment of cost reduction, real-time monitoring of drug quality delivered, clinical efficacy, efficency and safety is evident. This system allows administration of the medicine to patients as an alternative to the traditional 99% oxygen. The positive conclusion suggests a possible extension of the system to other corporate hospitals. References and/or Acknowledgements: Ossigeno 93%: valutazione di una tecnologia innovativa, sifo 2015. No conflict of interest